THE USE OF DIGITAL STORYTELLING TO ENHANCE THE SPEAKING SKILL OF THE ELEVENTH GRADE STUDENTS OF SMA SWASTA PALAPA MEDAN IN THE ACADEMIC YEAR OF 2020/2021 - Sinaga, Putri Desiana; Sari, Anna Stasya Prima; Sembiring, Novalina (Kairos English Language Teaching Journal, 2021)
This research was conducted in order to improve students’ speaking skill by using digital storytelling at SMA Swasta Palapa Medan. Digital storytelling is the combination of recount text, sound effects, music, images, videos and InShot Application. This is Classroom Action Research (henceforth, CAR). The research subjects of this CAR are the eleventh grade students of SMA Swasta Palapa Medan in Class MIPA in the Academic Year of 2020/2021. The research findings showed that teaching speaking skill through digital storytelling at SMA Swasta Palapa Medan could improve the students’ speaking skill. The result of each test showed that the students’ mean score in pre-test is 55.74 with 11% of the students got score ≥70, in formative test the mean score is 64,44 with 37% of the students got score ≥70, and in post-test the mean score is 81,11 with 93% of the students got score ≥70. The writer concluded that the use of digital storytelling could improve the speaking skill of SMA Swasta Palapa Medan. On the other hand, the students’ responses towards the method of the teaching sound good because above 80% of the students are interested, motivated and enthusiastic in learning English speaking skill through the use of digital storytelling.